The relationship between low birth weight (LBW) and the level of maternal knowledge about nutrition with the incidence of stunting in toddlers - Meilinda Rifka Novita; Sarwinanti Sarwinanti (International Journal of Health Science and Technology, 2022)
Low Birth Weight (LBW) is the weight of a baby at birth less than 2,500 grams (up to 2,499 grams). This study aimed to determine the relationship between low birth weight (LBW) and the level of maternal knowledge about nutrition with the incidence of stunting in toddlers. This study uses a correlation study method with retrospective and cross-sectional designs. The population in this study was stunting toddlers, and mothers who had stunting toddlers totaled 127 people with purposive sampling techniques obtained a total sample of 55 people. The instrument used in this study was a questionnaire—data analysis using Kendall’s tau test. The results showed p-value values of 0.032 and 0.618 for low LBW and the level of maternal knowledge about nutrition with stunting incidence. This study concludes that there is a significant relationship between low birth weight (LBW) and stunting incidence in toddlers, and there is no relationship that there was no meaningful relationship between the level of maternal knowledge about nutrition and the incidence of stunting in toddlers at the Tepus I Health Center.